Foreign Bodies in the rumen of the Sheep and Goats - Elkaseh , Rafi Mustafa; Hegazi, Ashraf abdel-hamed; Elhmri, Khaled M.A. Hussin (Al-Mukhtar Journal of Sciences, 2008)
Three Sheep &one Goat presented with anorexia,decreased in milk production ,weight loss & there were no significant findings on clinical examination . there were no lesions in the mouth & no other abnormalities were found. Adefinitive cause was not established .these animals were treated with systemic drugs to try and stimulat the appetite & antibiotics.The result was negative and the animals failed in response to trearment . They are treated by rumenotomy 12 hard Balls were collected from the Rumen in 1st case and 6 in the 2nd case the foreign bodies are plastics were the most common , rope & leather in 3rd&4th cases. When cut open these Balls were revealed to contain hair or wool or two which was enclosed in aleathery outer shell. The hair Balls occupied the most of the rumen leaving little for food , therefore were considered to be the cause of the inappetence & the hair Balls appear to be very unusual in sheep & goats.we made an additional examination of The foreign bodies in Rumen of sheep in El-beida from slaughter house.